Changing features of the Northern Hemisphere 500-hPa circumpolar vortex - Bushra, Nazla; Rohli, Robert V.; Li, Chunyan; Miller, Paul W.; Mostafiz, Rubayet Bin (Frontiers in Big Data, 2023)
The tropospheric circumpolar vortex (CPV), an important signature of processes steering the general atmospheric circulation, surrounds each pole and is linked to the surface weather conditions. The CPV can be characterized by its area and circularity ratio (R_c), which both vary temporally. This research advances previous work identifying the daily 500-hPa Northern Hemispheric CPV (NHCPV) area, R_c, and temporal trends in its centroid by examining linear trends and periodic cycles in NHCPV area and R_c (1979–2017). Results suggest that, counterintuitively, NHCPV area has increased linearly over time. However, a more representative signal of the planetary warming may be the temporally weakening gradient which has blurred NHCPV distinctiveness – perhaps a new indicator of Arctic amplification. R_c displays opposing trends in subperiods and an insignificant overall trend. Distinct annual and semiannual cycles exist for area and R_c over all subperiods. These features of NHCPV change over time may impact surface weather/climate.